The constituents of the resin of Euryops floribundus. N.E.Br. - Woolard, Graham Robert (Rhodes University, Faculty of Science, Department of Chemistry, 1966)
The aerial portions of the plant Euryops floribundus were extracted and shown to contain Euryopsonol and another sesquiterpenoid for which the name Euryopsol is proposed. An extraction of Euryops tenuissimus contained Euryopsol only. Euryopsonol, of empirical formula Câ‚ â‚… Hâ‚‚â‚€ Oâ‚ƒ, was previously shown to contain a hydroxyl group and a keto-group and to be doubly unsaturated. The hydroxyl group has been shown to be secondary, while the keto-group is â‹‰, Î², Î³, Î´-unsaturated, Spectroscopic and Mass spectrosmetric measurements showed euryopsonol to possess a furan ring and to be member of the eremophilane -9 of sesquiterpenoids . These proposals were confirmed by the conversion of euryopsonol to furanoeremophilone -9, thus establishing the stereochemistry at Câ‚„, Câ‚… and Câ‚ â‚€. This free hydroxyl group has been placed at Câ‚ƒ, but its stereochemistry is still unknown. Euryopsol, of empirical formula Câ‚ â‚… Hâ‚‚â‚‚ Oâ‚„, possesses an unstable furan ring and readily undergoes autoxidation, probably to a more stable Â¥-lactone. It contains two vicinal hydroxyl groups, one of which was placed by Mass spectrometry at Câ‚‰. If euryopsol possesses the eremophilane skeleton the other hydroxyl group must be at Câ‚ â‚€.
Keywords: Uncatalogued